2019
DOI: 10.3390/plants9010004
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Post-Harvest Stress that Affects Profiles of Volatile Organic Compounds and Gene Expression in Rocket Salad during Early Post-Harvest Senescence

Abstract: Once harvested, leaves undergo a process of senescence which shares some features with developmental senescence. These include changes in gene expression, metabolites, and loss of photosynthetic capacity. Of particular interest in fresh produce are changes in nutrient content and the aroma, which is dependent on the profile of volatile organic compounds (VOCs). Leafy salads are subjected to multiple stresses during and shortly after harvest, including mechanical damage, storage or transport under different tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(87 reference statements)
0
4
1
Order By: Relevance
“…By contrast, for mature leaves, stems and pods, Clemente-Villalba et al [33] only identified allyl ITC, 3-butenyl ITC and phenylethyl ITC. The presence and relative contribution of individual ITCs in wall rocket differs considerably to those reported in the rocket crops [11,22,26,29,[34][35][36][37][38][39][40]. Thus, three compounds identified in the present study for wall rocket (i.e., allyl ITC, benzyl ITC and phenylethyl ITC) were not reported in the literature for the related rocket crops (Table S1).…”
Section: Group Of Isothiocyanatescontrasting
confidence: 77%
“…By contrast, for mature leaves, stems and pods, Clemente-Villalba et al [33] only identified allyl ITC, 3-butenyl ITC and phenylethyl ITC. The presence and relative contribution of individual ITCs in wall rocket differs considerably to those reported in the rocket crops [11,22,26,29,[34][35][36][37][38][39][40]. Thus, three compounds identified in the present study for wall rocket (i.e., allyl ITC, benzyl ITC and phenylethyl ITC) were not reported in the literature for the related rocket crops (Table S1).…”
Section: Group Of Isothiocyanatescontrasting
confidence: 77%
“…In the experiments, six cuts occurred from mid-December to early May. Harvests were carried out when leaves of different treatments reached the commercial harvest stage (approximately until several serrated 10–12 cm leaves were present on each plant) [ 22 , 23 ]. Leaf samples were collected and weighed in order to determine yields and placed into a forced-draft oven at 65 °C to determine the dry matter percentage.…”
Section: Methodsmentioning
confidence: 99%
“…In each nest, five small depressions were made in which one seed of the red-or green-leaved lettuce (Lactuca sativa L.) was sown [38]. Such types of salad lettuces are commonly used to perform diverse studies on plant cultivation under different conditions [39][40][41][42], We experimented with two varieties of lettuce: the green-leaved lettuce called Azart (Prestizh Semena, www.pr-semena.ru, accessed on 1 May 2020, Russia), and the red-leaved lettuce called Robin (MoravoSeed, 1 May 2020, Czech Republic).…”
Section: Cultivation Of the Plantsmentioning
confidence: 99%